5(6+s)=45

Simple and best practice solution for 5(6+s)=45 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(6+s)=45 equation:


Simplifying
5(6 + s) = 45
(6 * 5 + s * 5) = 45
(30 + 5s) = 45

Solving
30 + 5s = 45

Solving for variable 's'.

Move all terms containing s to the left, all other terms to the right.

Add '-30' to each side of the equation.
30 + -30 + 5s = 45 + -30

Combine like terms: 30 + -30 = 0
0 + 5s = 45 + -30
5s = 45 + -30

Combine like terms: 45 + -30 = 15
5s = 15

Divide each side by '5'.
s = 3

Simplifying
s = 3

See similar equations:

| 8x-11y=33 | | -8x-36=-11x+4 | | x-14=8x+56 | | 5(x+6)+6=7(x+2)-4 | | 5y-10+y+60=5y+50-1y | | 33=-3(9+n) | | 9+b=3-2b | | 9x=4x-35 | | 3-3(x-6)=5x+12 | | 4y-21=-35+6y | | 15.50=26-79 | | 10x-45=3x-45 | | 6s-11=-23+9s | | 2x+13=10x+5 | | -17-3x=-50 | | -2v+10=2(5-v) | | x+3/2=9 | | (1-2q)-3=15 | | 435=32x+40 | | 6(3+2x)-3=63 | | -5x-16=-7+26 | | x+1/2=9 | | 2(3+6x)-1=41 | | 9+15z-7=9z+34-2z | | 9p+2.6=7.8+8p | | 7/1000= | | -42-4c=2c | | 9(4x-1)=3(12x+3) | | 56(7x-3)+78=6(7-3x)-78 | | 9/50= | | 9+4r-7=6r+14-4r | | 17w-2=15w |

Equations solver categories